(untitled) (International Journal of Food and Nutritional Sciences, 2020)
This study explores the nutritional profile and cultural significance of traditional dietary patterns in rural communities, emphasizing their health impacts and contribution to food security. Through dietary surveys, food sampling, and laboratory analysis, the research identifies nutrient-rich staples, areas of deficiency, and sociocultural influences on food consumption. Statistical approaches were used to analyze data against dietary reference intakes (DRIs), highlighting the strengths and weaknesses of traditional diets and providing a basis for integrating them into sustainable nutrition policies.